(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Diabetes mellitus (DM) is a major risk factor for the development of endothelial dysfunction which affects the ability of blood vessels to regulate vascular tone. The study aimed to investigate the mechanisms of vasodilator action of the anaesthetic agents ketamine and propofol in diabetic rat aorta. 30 male Sprague-Dawley rats were randomly divided into two equal groups: (i) non-diabetic control (ii) Streptozotocin-induced diabetic group. DM was induced by a single intra-peritoneal injection of streptozotocin at 50 mg/kg body weight. Blood samples were taken from the tail vein after 24 hours and tested for glucose level using an automated glucose analyser. A blood glucose ≥10 mmol/L confirmed hyperglycaemia and the development of DM. Rats were sacrificed, and the aortae excised. The vascular responses of aortic rings from both groups to ketamine, propofol in the presence of vasoactive agents were studied using standard organ bath procedures. Ketamine and propofol reduced Phe-induced contraction similarly in the diabetic and control groups. Barium chloride, attenuated the relaxation response to propofol in diabetic aorta when compared to ketamine. 4-aminopyridine significantly attenuated the relaxation response to ketamine and propofol in diabetic aorta. Glibenclamide, significantly reduced ketamine-induced relaxation in diabetic aorta when compared to propofol. Activation of K+ channels with nicorandil or NS1619 did not affect the relaxation response to ketamine or propofol in diabetic aorta. The results recommend that propofol can be effective in mitigating the consequences of hemodynamic instability in glibenclamide treated diabetics when compared to ketamine. This response is mediated by propofol-induced inhibition of intracellular calcium influx.